Aerobic fitness and its relationship with growth and maturation processes - Edilson Serpeloni Cyrino; Alexandre Hideki Okano; Karina Elaine de Souza Silva; Leandro Ricardo Altimari; Valfredo Ribeiro Dórea; Sérgio Miguel Zucas; Roberto Carlos Burini (Journal of Physical Education (Maringá), 2008)
The aimf of this paper is to provide information concerning aerobic fitness and then relate the behavior of aerobic strength with growth and maturation processes, since the aerobic metabolism during the practice of physical exercises has been the target of research along the last decades, both under the perspective of health promotion and the improvement of the athletic performance. In that sense, information about aerobic fitness has provided the evaluation of the cardiorespiratory system functioning, the training efficacy control, the determining of the effort relative load, besides determining the individual’s energy expenditure in different age groups, both male and female, and with differential levels of physical fitness. The main indexes used in this purpose have been the maximal oxygen consumption (VO2max) or the peak oxygen consumption (VO2peak). However, several factors may influence such indexes, being either determinant or retraint of the motor performance, mostly in predominantly aerobic activities. Among such factors the emphasis is on growth and maturation processes, which can explain many of the differences found in the behavior of different individuals submitted to similar physical efforts, providing thus a more consistent analysis of the differences in the motor performance, particularly of young male and female.